Digital Educational Technologies for Enhancing Methodological Competence of Pre-Service Foreign Language Teachers: A Quasi-Experimental Study in Ukrainian Higher Education - Ivetta Depchynska; Inna Stakhova; Antonina Pak; Olha Dolhusheva; Anna Pikalova (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study aims to evaluate the effectiveness of digital educational technologies in developing the methodological competence of pre-service foreign language teachers through a quasi-experimental approach comparing experimental and control groups. Methodology: This study employed a quasi-experimental pre-test–post-test design with control and experimental groups. Data were collected using proprietary 40-item tests administered via Moodle (version 4.0). Statistical analysis included Student’s t-test, Pearson’s chi-square test, and effect size (Cohen’s d, Cramer’s V). The intervention integrated digital tools such as Google Classroom, Kahoot!, Quizlet, and Padlet. Main Findings: The findings indicate a positive but limited improvement in methodological competence among participants in the experimental group. The most notable increase occurred in the cognitive (8.1%) and motivational (9.5%) components, followed by reflective (6.8%) and activity-based (4.1%) components. Statistical analysis revealed significant differences only in the cognitive component (p < 0.05), while other components showed small effect sizes without statistical significance. Novelty/Originality of this study: This study provides an integrated digital-methodological model grounded in TPACK and constructivist theory, empirically validated through a quasi-experimental design. It uniquely examines the differential impact of digital technologies on specific components of methodological competence, offering new insights into targeted competence development in foreign language teacher education within the Ukrainian higher education context.